Sodium channel blockers in Brugada syndrome - El-Battrawy, Ibrahim; Borggrefe, Martin; Lang, Siegfried; Zhou, Xiao-Bo; Akın, Ibrahim (Europace, 2018)
The article by Florez et al.1 published in Europace determining the value of the sodium channel blocker flecainide in Brugada syndrome (BrS) presented very inte